ASEAN Economic Community And Small-Medium Enterprises: An English School Perspective - Robertua, Verdinand (Universitas Muhammadiyah Yogyakarta, 2016)
Accounting for 30-60% of GDP of ASEAN member states and the largest source of employment for all economic actors, small medium enterprises is a very important economic actor in Southeast Asia. The SME sector in ASEAN, however, is confronted with a wide-range of structural, financial and other challenges, among which are limited access to finance, technologies and markets. ASEAN has many important roles in developing SMEs. ASEAN institutions can guide, direct, and fund many development programmes related to SMEs. Moreover, AEC, a new set of regional liberalization package, will have important consequences to SMEs’ growth in the ASEAN member states. Therefore this paper will ask the impact of AEC to SMEs in ASEAN member states using English School Theory. It also asks the role of ASEAN in promoting SME development toward AEC. In this paper, interview and content analysis will do as the main data source. This paper concluded that ASEAN has developed a comprehensive empowerment plan through Strategic Action Plan for ASEAN SME Development but lack of coordination between ASEAN institutions has hindered the full implementation of the plan.